Legal Arrangements Regarding Polri's Disciplinary Actions in Carrying Out Their Duty as A Security Personnel - Arif Kurniawan; Endang Kusuma Astuti (Publikasi Indonesia, 2023)
The Indonesian National Police (POLRI) is responsible for maintaining public security and order, as well as serving and protecting the community. However, there have been instances where members of the police force have clashed with civilians while carrying out their duties. This study employs normative legal research, focusing on secondary data obtained from various sources. The legal methodology approach is utilized to examine relevant regulations and guidelines related to the legal issues at hand. According to Article 2 of Unofficial Law No. 3 of 2003, which pertains to the Specialized Execution of General Legal Foundations for members of the Indonesian National Police, the law enforcement process for police officers is carried out within the procedural regulations applicable in general court proceedings. Thus, if a member of the National Police is reported to have committed a crime, they are processed by the Criminal Investigation Unit. Article 12 (4) of the Police Professional Code of Conduct stipulates administrative sanctions, which include 1) transferring duties to a different position, 2) transferring duties to different areas, 3) honorable discharge, or 4) dishonorable discharge. Transfers of positions and areas serve as administrative sanctions for police officers who have violated the Professional Code of Conduct, involving either demotion (transfer to a lower position) or reassignment to a different place/region. Honorable discharge or dishonorable discharge, on the other hand, are administrative actions taken against police officers who have demonstrated a violation of the Professional Code of Conduct.